Hubungan Antara Self-Esteem, Self-Confidence, Self-Efficacy dan Resiliensi Akademik Pada Mahasiswa Baru - Muarif, Ahmad Syamsul; Al Musafiri, M. Rizqon (Institut Agama Islam Negeri Padangsidimpuan, 2023)
The purpose of this study was to determine the relationship between self esteem, self confidence, self efficacy on academic resilience in new students at Darussalam University. The method in this study uses non-experimental correlation with a total of 67 students. Data collection using a self esteem scale developed based on the Rosenberg Self Esteem scale (RSES) theory, a self confidence scale developed with Shrauger and Schohn's theory known as the Personal Evaluation Inventory (PEI) adapted to educational conditions in Indonesia, developed with a self Efficacy scale using the General Self-Efficacy Scale. While for resilience using the Resilience Evaluation Scale (RES) which is adjusted to education in Indonesia. The research findings showed that students tend to have low self esteem, high self confidence, high self efficacy, and higher student academic resilience. The relationship between self esteem, self confidence, self efficacy to academic resilience shows a strong relationship.